The effect of acute respiratory events and respiratory stimulants on EEG-recorded brain activity in neonates: a systematic review - Usman, F; Marchant, S; Baxter, L; Salihu, HM; Aliyu, MH; Adams, E; Hartley, C (Elsevier, 2023)
Objective: We conducted a systematic review to investigate electroencephalography (EEG) changes during periods of acute respiratory events such as apnoea and the effect of respiratory stimulants on EEG features in infants.